THE COMPARISON OF SCIENCE PROCESS SKILLS BETWEEN PROBLEM BASED LEARNING APPLICATION COMBINED WITH INFORMAL DEBATE AND CONVENTIONAL LEARNING AT X GRADE STUDENTS AT SMA MUHAMMADIYAH 1 KARANGANYAR IN ACADEMIC YEAR 2013/2014 - Suciati, Desi W P, Harlita (Pendidikan Biologi, 2015)
The purpose of this research is to know the difference of science process skills between problem based learning models combined with informal debate and conventional learning at X grade students at SMA Muhammadiyah 1 Karanganyar in academic year 2013/2014. This study was a quasi experimental research. The research design was used post-test only nonequivalent control group design. This research applied problem based learning models combined with informal debate in experimental group and contextual with based on problem?s discussion in comparator group. The population of this research was all of X grade students at SMA Muhammadiyah 1 Karanganyar in academic year 2013/2014. Sampling techniques used cluster sampling that choosed X.4 as experiment group and X.11 as control group. Techniques of collecting data were test and non-test methods. The test method included science process skills test. The non-test method included observation and documentation.  The hypotheses analyzed by t-test.  The result of research assert that average values of science process skills at experiment group (74,4) higher than comparator group (63,8).  The result of statistic analysis used hypotheses test assert that Sig. < 0,05 is 0,000 which there is differences between problem based learning application combined with informal debate and conventional learning. This research concluded that there is differences of science process skills between application of problem based learning models combined with informal debate and conventional learning at X grade students at SMA Muhammadiyah 1 Karanganyar in academic year 2013/2014. Key words : problem based learning, informal debate, science process skills.